Tinjauan Yuridis Terhadap Sistem Transparansi dalam Pengelolaan Anggaran Pendapatan dan Belanja Daerah (APBD) Bidang Kelautan dan Perikanan di Kabupaten Jepara Tahun 2013 - Aini Rahmania Rahmania (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2014)
Transparency is an important elementin the frame work of realization of goodgovernance. The principle of transparency determines that each activity of management ofthe regional budget should be accountable to the people as the supremes overeignty.Related to that statement, The Government of Jepara Regency is obligated to managethe Regional Budgetin open,efficient and fair. But from the datain 2013 the budgetdepartment of Marine and Fisheries Government of Jepara Regency absorbed only 45,7percentofthe budget Rp.17.229.808.000 with indirect expenditure category budgetedRp.3.163.988.000 absorbed Rp.2.930.818.519 and direct expenditure budgetedRp.14.065.820.000 and just absorbed Rp.4.939.324.3766. The results showed thatthe implementation of transparency in the RegionalBudget Management of Marine andFisheries of Jepara Regency in 2013 has not been implementedoptimally. It is provedthat the financial information published uncompletedand is very difficult to access andhas not complywith a standard requestby Law No. 28, 1999 about StateImplementation of Clean and Free of Corruption, Collusion and Nepotism, Law No.14, 2008 aboutDisclosure Public Information, Law No. 25, 2009 about PublicAttendant, Information Commission Regulation No. 1, 2010 about PublicInformation Service Standards, Ministry of Home Affairs in 2012 Instruction No.188.52 / 1797 / SJ about Improving Transparency Regional Budget Management.Furthermore, in terms of the realization of the use of budgets, in 2013 Regional Budgetabsorption is relative low and does not show the results and benefits to coastalcommunities that appropriate with the mandate of Law Number 12, 2008 aboutalteration the Second Amendment Law No. 32, 2004 about Regional Government.In the implementation of transparency of the Regional budget management of MarineAffairs and Fisheries encountered several obstacles, some of these obstaclesare weakquality of human resources and the availability of budgets are not appropriate.